Can a cup of black coffee enhance cognitive function and short-term memory? - Dinesh Vedanathan Syce (Al Ameen Medical College, 2019)
Background: The stimulatory effects of coffee on the central nervous system (CNS) have been well studied. There exists, however, no conclusive data on the effects of the consumption of coffee on short-term memory. Objectives: This study's objective was to determine the effects of coffee on short-term memory and on certain recent tests of cognitive function such as digit symbol substitution test (DSST) and letter cancellation. Methods: The study involved a single group of fifty male subjects aged between 18 and 25. The subjects underwent a set of baseline tests that included estimation of visual and auditory reaction time, tests of cognitive function such as letter cancellation and digit symbol substitution test (DSST), and tests of short-term memory such as immediate word and immediate object recall. They were then given a cup of black coffee and fifteen minutes later the same set of tests were performed. Results: It was observed that there was a significant shortening of the visual (p<0.001) and auditory reaction time (p<0.001), and the time taken for letter cancellation (p<0.001) and DSST (p<0.001) after coffee. There was an increase in the number of objects recalled that approached statistical significance (p=0.082), but no obvious effect on the number of words recalled. Conclusion: The above observations seem to indicate that coffee improves cognitive and psychomotor function, may improve the ability to recall visual information but plays no role in the recall of auditory information.